2019
DOI: 10.1016/j.scitotenv.2019.03.176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digestate application on microbial respiration and bacterial communities' diversity during bioremediation of weathered petroleum hydrocarbons contaminated soils

Abstract: Revised version resubmitted to Science of the Total Environment Highlights Digestate application with bulking agent or immobilized bacteria improve TPH removal Digestate effect on soil respiration depends on soil texture Sewage sludge digestate contains high concentrations of alkB genes *Manuscript (double-spaced and continuously LINE and PAGE numbered)-for final publication Click here to view linked References Highlights Digestate application with bulking agent or immobilized bacteria improve TPH removal Dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 50 publications
3
15
1
Order By: Relevance
“…Although we did not study the influence of natural attenuation on hydrocarbon removal in great details, our results show relatively low effectiveness of this approach compared to other reports [65,[76][77][78]. In turn, other authors also noticed insufficient effects of naturally occurring processes as a remediation strategy [79,80].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Although we did not study the influence of natural attenuation on hydrocarbon removal in great details, our results show relatively low effectiveness of this approach compared to other reports [65,[76][77][78]. In turn, other authors also noticed insufficient effects of naturally occurring processes as a remediation strategy [79,80].…”
Section: Discussioncontrasting
confidence: 86%
“…Natural attenuation occurs in environments, but at least one of following conditions must be fulfilled: (1) it should be the adequate concentration of available P and N, and/or (2) the soil texture should allow bacteria to have facilitated access to hydrocarbons and oxygen. In laboratory conditions, the latter could be achieved by passing the soil through a sieve [76][77][78]. However, this practice was not applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Single research [38] indicated high efficiency of digestate as a potential nutrient and microbial seeding for bioremediation of petroleum hydrocarbon contaminated soils. Addition of digestate together with saw dust decreased aggregates size and improved soil respiration.…”
Section: The Results Of the Digestate Application As Biostimulantmentioning
confidence: 99%
“…The prokaryotic community structure of the treatments reported by Wang [82] was evaluated, and the results showed that Mix2 treatment, in which low NO 3 − risk and high nematode suppression were confirmed, was separated from the other treatments, indicating that a specific microbial community was developed in the treatment (Figure 2). Several papers have already reported that the application of biogas digestate affected the community structure of bacteria and fungi [122][123][124]. In general, organic amendment stimulates a broad range of (micro) organisms involved in the soil food web, many of which are potential predators, such as diplogasterid [125] and dorylaimid [126], or invertebrate antagonists, such as enchytraeids and earthworms [127].…”
Section: Effect Of Biogas Digestate Application On Root-knot Nematodementioning
confidence: 99%